Analysis of the Influence of Financial Literacy Determinants on Undergraduate Students in Yogyakarta - Gita Sastri; Katiya Nahda (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2023)
This research aims to examine the factors influencing students' financial literacy using variables such as gender, age, field of study, participation in financial management classes, father's education, mother's education, amount of pocket money, and Grade Point Average (GPA). The study population comprises active students from different universities in Yogyakarta. A survey approach was employed, including distributing questionnaires to 216 undergraduate students associated with Universitas Islam Indonesia. The statistical tool used to test the hypothesis in this study was multiple linear regression analysis with SPSS 25. The outcomes indicated that gender and age indeed impact financial literacy. In contrast, variables including a field of study, participation in financial management classes, father's education, mother's education, pocket money, and GPA do not influence financial literacy.